Association of oxidative balance score with all-cause and cardiovascular mortality in overweight and obese - Ying, Shuxin; Ding, Hongyan; Chen, Yanjin; Zheng, Su (Frontiers in Nutrition, 2025)
BackgroundThe oxidative balance score (OBS) combines diverse dietary components with lifestyle factors to comprehensively evaluate oxidative stress. The investigation focuses on the link between the OBS and mortality outcomes, including cardiovascular and all-cause deaths, in overweight and obese individuals.MethodsThe analysis utilized data from the National Health and Nutrition Examination Survey (NHANES), covering the period from 1999 to 2018. Mortality information, categorized into all-cause and cardiovascular deaths, was gathered from the National Death Index (NDI). Kaplan–Meier survival analysis, along with multivariate Cox regression and restricted cubic spline (RCS) modeling, were utilized to explore the link between OBS and mortality risks. Subgroup analysis and sensitivity analysis were used to assess the robustness of the results and possible effect modifiers. Mediation analysis identifies pathways through which the independent variable affects the dependent variable.ResultsIn this study, 26,219 participants with overweight or obesity were enrolled, with an average age of 49.8 ± 17.4 years. During a median follow-up duration of 115 months, 2,239 participants (8.5%) died, including 837 (3.2%) from cardiovascular disease. According to Kaplan–Meier analysis, mortality was highest among participants in the lowest OBS quartile (Q1) and lowest among those in the highest quartile (Q4). Participants in the fourth OBS quartile experienced a 21.7% decrease in the risk of mortality from all causes and a 29.5% decrease in cardiovascular mortality risk, according to fully adjusted results, compared to those in the first quartile. These results were validated through subgroup analyses. The analysis of RCS revealed a notable inverse association between OBS and mortality outcomes. Mediation analysis indicates that white blood cell count (WBC) and gamma-glutamyl transferase (GGT) serve as significant mediators in the association between OBS and mortality risk.ConclusionElevated levels of OBS were strongly linked to reduced potential for both cardiovascular and all-cause mortality among individuals who are overweight or obese.